Antibody engagement with amyloid‐beta does not inhibit [11C]PiB binding for PET imaging - Xiong, Mengfei; Dahlén, Amelia; Roshanbin, Sahar; Wik, Elin; Aguilar, Ximena; Eriksson, Jonas; Sehlin, Dag; Syvänen, Stina (Journal of neurochemistry, 2024)
The elimination of amyloid‐beta (Aβ) plaques in Alzheimer's disease patients after treatment with anti‐Aβ antibodies such as lecanemab and aducanumab is supported by a substantially decreased signal in amyloid positron emission tomography (PET) imaging. However, this decreased PET signal has not been matched by a similar substantial effect on cognitive function. There may be several reasons for this, including short treatment duration and advanced disease stages among the patients. However, one aspect that has not been investigated, and the subject of this study, is whether antibody engagement with amyloid plaques inhibits the binding of amyloid‐PET ligands, leading to a false impression of Aβ removal from the brain. In the present study, tg‐ArcSwe mice received three injections of RmAb158, the murine version of lecanemab or phosphate‐buffered saline (PBS) before the administration of the amyloid‐PET radioligand [11C]PiB, followed by isolation of brain tissue. Autoradiography showed that RmAb158‐ and PBS‐treated mice displayed similar [11C]PiB binding. Moreover, the total Aβ1–40 levels, representing the major Aβ species of plaques in the tg‐ArcSwe model, as well as soluble triggering receptor on myeloid cells 2 (sTREM2) levels, were similar in both groups. Interestingly, the concentration of soluble Aβ aggregates was decreased in the RmAb158‐treated group, along with a small but significant decrease in the total Aβ1–42 levels. In conclusion, this study indicates that the binding of [11C]PiB to Aβ accurately mirrors the load of Aβ plaques in the brain, aligning with how amyloid‐PET is interpreted in clinical studies of anti‐Aβ antibodies. However, early treatment effects on soluble Aβ aggregates and Aβ1–42 levels were not detected. We investigated whether the anti‐amyloid‐beta (Aβ) antibody lecanemab affects amyloid‐positron emission tomography (PET) ligand binding, potentially giving a false impression of plaque removal in Alzheimer's disease. Mice with Aβ pathology received three injections of a murine version of lecanemab during two weeks to maximize Aβ plaque binding without plaque removal. Treatment did not decrease amyloid‐PET ligand [11C]PiB binding or plaque load, but decreased soluble Aβ aggregates. This suggests that amyloid‐PET accurately reflects plaque load but may not capture early treatment effects on soluble Aβ. Understanding this is crucial for interpreting clinical studies of anti‐Aβ antibodies in Alzheimer's disease.